Peran Koherensi Keluarga terhadap Resiliensi Keluarga yang Memiliki Anak Cerebral Palsy - Mayang Meutiasari; Melok Roro Kinanthi; Alabanyo Brebahama (Jurnal Ilmiah Psikologi MIND SET, 2020)
Families of children with cerebral palsy are prone to experience stress in life. To adapt optimally, its is important to ensure they are resilient, by knowing factor that contribute to family resilience. The aim of this study is to examine whether family sense of coherence affect family resilience among families of children with cerebral palsy. With quantitative approach, this study involved 50 participants, selected by convenience sampling. We applied Family Sense of Coherence Scale to assess family sense of coherence and Walsh Family Resilience Questionnaire to assess family resilience. The regression analysis revealed family sense of coherence has significant positively contribution to family resilience among participants.The contribution of family sense of coherence to family resilience was 26,6%. This result implied family strength-based approached should be considered to empower families of children with cerebral palsy.